Influence of Al and F surface modifications on the sudden death effect of Si-Gr/Li1.2Ni0.2Mn0.6O2 Li-Ion cells. (20th December 2021) - Peralta, David; Salomon, Jérémie; Reynier, Yvan; Martin, Jean-Frédéric; De Vito, Eric; Colin, Jean-François; Boulineau, Adrien; Bourbon, Carole; Amestoy, Benjamin; Tisseraud, Celine; Pellenc, Roger; Ferrandis, Jean-Louis; et al.
Highlights: Dissolution, migration and deposition (DMD process) is observed in silicon-graphite/lithium rich Si-Gr/Li1.2Ni0.2Mn0.6O2 systems. AlF3 coating do not avoid the manganese dissolution process. Al and F elements dope the lithium layered surface structure. Abstract: The dissolution, migration and deposition (DMD process) of transition metal ions during cycling is a well-known phenomenon reported in literature especially concerning high manganese spinel cathode material. The main approach to solve this issue consists in coating or doping the particles surface with electrochemically inert cations and/or anions. In this study, we describe a DMD process mechanism which happens in the silicon-graphite/lithium rich layered oxide (Si-Gr/Li1.2 Ni0.2 Mn0.6 O2 ) systems. This phenomenon leads to a sudden death effect of the cell after 25 cycles. AlF3 coating is envisaged to limit the cation dissolution from the positive electrode: we highlight that our synthesis finally results in improving the electrochemical performances of lithium rich layered oxides by offering an Al/F doped surface. Despite this improvement, the coating fails, on the other hand, to stop the transition metal cations dissolution, especially in Li-ion cells (Si-Gr as anode). Graphical abstract: Image, graphical abstract